Questioni di facciata? Il colore dello spazio, lo spazio del colore e la bellezza del bianco - Fachechi, Grazia Maria (Opus Incertum, 2017)
A difficult aspect to put into context, colour is not of secondary importance, but rather is of primary consideration in the design of a building as to how it will be perceived, starting with its facade. White as a colour (whether the sum of all colors or their very absence and negation) seems to have been the preferred choice of architects throughout the ages. It was determined by the materials in use but also by cultural-symbolic reasons. White was mistakenly believed to be “the colour” of Classical Antiquity, but only because of the decay of time and the loss of pigments that characterized, for example, the pediment in Classical temples. That’s why it was considered particularly suited for expressing the ideal of formal perfection, beginning with the Renaissance, continuing with the Baroque, Neo-Palladianism, Neo-Classicism, as well as the architecture of the fascist period. So rare in Antiquity and in the Middle Ages, eras characterized by a tendency for a more or less insistent use of polychromy, in which white was just one of many possible colours, the monochrome modality becomes a growing option. However long seen as a reference to Classical Antiquity, and from a philological point of view due to the Modernist movement the negation of historical truth or the recognition of colour as aesthetic error, white has risen as a contemporary symbol. It is considered on the one hand perfect for expressing a neutral state which doesn’t speak but is spoken about, allowing its context or content to emerge. While on the other hand it is perfect for the search for other dimensions outside of time and the surrounding space.